Experts on the defensive: The Tsiganologue versus Romani activism (1959-1973) - Begoña Barrera López (Culture & History Digital Journal)
This article discusses the figure of the Tsiganalogue, the expert on the “Tsigane question,” in post-World War II France. Specifically, it analyses the role played by one of these experts in the police persecution of Roma ethnic activism during the 1960s and early 1970s. Drawing on this case study, its objective is two-fold: firstly, to show the central role that Tsiganalogues played in the hounding of the Romani movement; secondly, to explain how the self-perceptions of these experts (of their authority and role) were decisive factor in their interventions with the public authorities. The article draws on a wide range of sources from the French Ministry of the Interior and the Ministry of Health and Population. It is structured in five parts: the first briefly defines and explains the concepts of expert, expert knowledge and ethnicity; the second describes the context and profile of the main agents studied (the Tsiganalogues, Romani activists and the French police); the third and fourth parts examine in extenso the primary documentation; and finally, the fifth part offers a reflective summary of the profile of the Tsiganalogue.